AB1067 Ultrasound Assessment of Rheumatoid Arthritis Patients on Biological Therapy Using A 12 Joint Score – Sonographic Findings. (9th June 2015) - Cerqueira, M.; Teixeira, F.; Sousa Neves, J.; Peixoto, D.; Costa, J.A.; Afonso, M.C.
Abstract : Background: Ultrasound (US) evaluation is becoming increasingly more used to assess patients with Rheumatoid Arthritis and other rheumatic diseases, not only for diagnostic purposes, but also to assess disease activity and support therapeutic decisions. Objectives: Identify the inflammatory US findings on RA patients on biological DMARDs (bDMARDs) using a 12-joint assessment and an US score based on the presence of synovitis or tenosynovitis and Power Doppler (PD) signal. Methods: Forty one patients diagnosed of Rheumatoid Arthritis, on bDMARDs, followed in our day-care hospital unit, were evaluated using a 12 joint US assessment (bilateral elbow, wrist, 2nd metacarpophalangeal (MCP), 3rd MCP, knee, ankle) within 3 hours of the routine clinical examination. The US assessment was performed by the same Rheumatologist, blinded to the clinical and laboratory findings; the Rheumatologists who made the clinical assessment were blinded to US evaluation. Both synovitis and PD were graded semi quantitatively from 0-3; the final US score was the sum of the highest synovitis and PD scores at each joint. Joints surgically replaced were excluded. Results: The mean years of disease since diagnosis was 13.97±5.76. Fifteen patients were treated with Etanercept, 6 with Adalimumab, 6 with Tocilizumab, 5 with Infliximab, 5 with Rituximab and 4 with Golimumab. The mean clinically assessed DAS28 was 3.07±1.16. A total of 484 joints were assessed. Synovitis and PD were found in 24% and 3% of the ankles, 21% and 17% of the wrists, 19% and 9% of the 2nd MCP, 7% and 2% of the 3rd MCP, 6% and 0% of the knees and 5% and 0% of the elbows, respectively. The assessment of US disease activity in the ankle was largely due to tenosynovitis of the tibialis posterior which was found in 19% of the cases. The mean US score was 3.22±5.12 with a range from 0 to 30, with a mean synovitis score of 2.51±4.24 and a mean PD score of 0.71±1.27. Conclusions: The ankle, a joint not included in the DAS28, was the joint that expressed more frequently US disease activity, mainly due to the presence of tenosynovitis of the tibialis posterior . Tenosynovitis of this tendon may be difficult to clinically detect and is associated with a progressive flat foot deformity. The wrist and 2nd MCP were the joints with highest combined synovitis and PD score, which may be in agreement with the known frequent erosive and destructive evolution of these joints in RA patients. References: Naredo, E., et al., Validity, reproducibility, and responsiveness of a twelve-joint simplified power doppler ultrasonographic assessment of joint inflammation in rheumatoid arthritis. Arthritis Care & Research, 2008. 59(4): p. 515-522. Disclosure of Interest: None declared